Effect of a-Alkyl Substituents in the Solvolysis of Cumyl Chloride in 90% Aqueous Organic Solvents - Balachandran, S.; Sudha Devi, R. (Asian Journal of Chemistry, 2016)
The substitution of methyl group of cumyl chloride by bulky alkyl groups reduces the rate of solvolysis in 90% aqueous organic solvents. The difficulty in attaining coplanarity at the transition state reduces the delocalization of the charge by resonance and thus retards the rate of solvolysis. The linear plot obtained when log k1 is plotted against Charton's steric parameter ‘n’ (upsilon) indicates the rate is controlled by steric factors rather than the electronic factors. The similar values of reaction constant ‘r+’ in the para substituted compounds of cumyl chloride and ethylmethylbenzyl chloride indicate the steric contribution of ethyl group is negligible.